WARUNG MADURA IN DKI JAKARTA: A PUBLIC MANAGEMENT CASE OF MIGRATING MADURESE TRIBE - Hikmah, Nurul; Tando, Cahyoko Edi (Sanata Dharma University, 2025)
For the Madurese tribe, one of the largest ethnic groups in Indonesia, DKI Jakarta Province has become one of the destinations for people to migrate in the hope of improving their economy. It is done by creating various new businesses, one of which is Madura Store or Warung Madura. However, this creates new problems in the economy as its non-standard operating hours certainly increase competition in the same type of business. Qualitative methods were used in this study. The results show that the Madurese have social capital that can be utilized to support national development. Through bonding, they can unite in one tribal group due to the similarity of characteristics, language, culture, religion, and even the same fate abroad. Then, the bridging aspect supports them in having a community that organizes various communications and maintains the solidarity of every Madurese migrant in DKI Jakarta, thus they can build networks vertically and horizontally. Moreover, the linking aspect allows them to create a wide relationship and social network without having to form a concrete community.